The amygdalo-motor pathways and the control of facial expressions - Gothard, Katalin M. (Frontiers in Neuroscience, 2014)
Facial expressions reflect decisions about the perceived meaning of social stimuli emitted by others and the expected socio-emotional outcome of the reciprocating expression. The decision to produce a facial expression emerges from the joint activity of a network of structures that include the amygdala and multiple, interconnected cortical and subcortical motor areas. Reciprocal transformations between sensory and motor signals give rise to distinct brain states that promote, or impede the production of facial expressions. The muscles of the upper and lower face are controlled by anatomically distinct motor areas and thus require distinct patterns of motor commands. Concomitantly multiple areas, including the amygdala, monitor the ongoing overt behavior (the expression of self) and the covert, autonomic responses that accompany emotional expressions. Interoceptive signals and visceral states, therefore, should be incorporated into the formalisms of decision making in order account for decisions that govern the receiving-emitting cycle of facial expressions.